Gardenia volkensii K. Schum. (Rubiaceae): Review of Medicinal uses, Phytochemistry and Biological Activities - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Gardenia volkensii K. Schum. is a shrub or small tree widely used as traditional medicine throughout its distributional range in tropical Africa. This study is aimed at providing a critical review of the medicinal uses, phytochemistry and biological activities of G. volkensii. Documented information on the medicinal uses, phytochemistry and biological activities of G. volkensii was collected from several online sources, which included Scopus, Google Scholar, PubMed and Science Direct. Additional information was gathered from pre-electronic sources such as book chapters, books, journal articles and scientific publications sourced from the university library. The articles published between 1972 and 2020 were used in this study. This study showed that the species is widely used as emetic and protective charm, and as traditional medicine for infertility, sore eyes, sexually transmitted infections, headache, gastro-intestinal infections, earache, convulsions, epilepsy and respiratory infections. Phytochemical compounds identified from the species include aldehydes, benzenoids, cinnamates, coumarins, essential oils, fatty acids, flavonoids, iridoids, phenolics, phytosterols and triterpenoids. Pharmacological research revealed that G. volkensii extracts and compounds isolated from the species have antibacterial, antifungal, antioxidant, mutagenic and antimutagenic and cytotoxicity activities. Future research on G. volkensii should focus on detailed phytochemical evaluations including toxicological, in vivo and clinical studies to corroborate the traditional medical applications of the species.